Visual research an introduction to research methods in graphic design - Noble, Ian; Bestley, Russell (London Fairchild Books, an imprint of Bloomsbury Publishing PIc, 2016)
Packed with more than 200 colour illustrations, Visual Research explores a range of research methods that can be used by graphic designers and visual communicators in the development of clear and purposeful design solutions. The book introduces key terms and theories that underlie design research; examining the importance of visual grammar and design literacy, audience, communication theory and semiotics. Each chapter features case studies that demonstrate how the use of research methods can form the basis of effective visual communication and design problem solving, eschewing end product analysis for a discussion of the way research feeds into the design process. The third edition features new case studies in each chapter, updated design exercises and a new chapter on design-led tools and information design methods, in relation to both print and on-screen design--Provided by publisher.
Includes bibliographical references (page 218) and index.
Keywords: Graphic arts -- Research; Design -- Research